Photodegradation of Rhodamine B in Presence of CaO and NiO-CaO Catalysts - Tobias Kornprobst; Johann Plank (International Journal of Photoenergy)
A CaO catalyst was prepared by mild calcination (650°C) of facilely precipitated Ca(OH)2 and compared to an NiO-CaO catalyst obtained from an Ni(OH)2/Ca(OH)2 coprecipitate as a precursor. Both catalysts degraded rhodamine B (RB) effectively when exposed to ultraviolet light but exhibited slower degradation under visible light conditions. Under UV light, CaO was more effective than NiO-CaO, while in visible light, the opposite was observed. A mechanistic study revealed no influence of the specific surface area of the catalysts on RB degradation, no adsorption of RB on the positively charged surfaces of the catalysts, and only incomplete degradation of RB. Consequently, both materials represent nonconventional photocatalysts.